Edukasi Kesehatan dan Gambaran Pengetahuan Masyarakat tentang Tuberkulosis di Car Free Day - Novita Dhewi Ikakusumawati; Zahro Isna Fauziyah; Hana Anwar Baraja; Fatimah Nur Khasanah (Universitas Pahlawan Tuanku Tambusai, 2026)
Tuberculosis (TB) remains a major public health problem in Indonesia, with a considerable number of cases reported. A paucity of public literacy regarding the symptoms, transmission, and prevention of TB has the potential to impede efforts to eradicate the disease. This community service activity was designed to provide education and assess the public's knowledge about tuberculosis during Car Free Day in Surakarta. The methodology entailed a combination of face-to-face education, utilizing leaflets and direct interaction, followed by an evaluation through a questionnaire containing nine questions, including definition, etiology, symptoms, prevention, examination, duration of treatment, and contact investigation of tuberculosis. A total of 22 respondents participated in this activity. The results indicated that the majority of respondents demonstrated a high level of knowledge regarding the definition of TB (90.9%), its etiology (86.4%), proper cough etiquette (95.5%), and the duration of treatment (95.5%). However, the comprehension of tuberculosis symptoms in children (45.5%), the BCG vaccination (54.5%), and the contact investigation (18.2%) remained inadequate, highlighting the need for targeted educational interventions to improve understanding in these critical areas. The implementation of health education in public spaces is of paramount importance and must be carried out in a continuous manner to effectively increase public awareness regarding the prevention and early detection of tuberculosis.